2015
DOI: 10.1200/jco.2015.33.7_suppl.71
|View full text |Cite
|
Sign up to set email alerts
|

The predictive value of ARv7 expression in localized prostate caner treated with abiraterone, degarelix, and bicalutamide.

Abstract: 71 Background: Androgen receptor splice variants (ARvs) are upregulated in response to castration, and can activate transcription in the absence of ligand. Recent evidence indicates that CTC ARv7 expression is an accurate predictor of absence of response to abiraterone and enzalutamide, providing strong clinical support for ARv7 upregulation as potential overarching mechanism of castration resistance. There is however limited data regarding the expression of ARv7 in clinically localized prostate cancer (CaP),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Efstathiou et al showed that the presence of nuclear AR-V7 correlated with residual cancer burden in the resected specimen in patients treated with a 3-month neoadjuvant ADT ± ABI [16]. Conversely, another pilot study reported that while AR-V7 expression was detected in all 16 included patients with clinically localized high-risk PCa, prior to receiving neoadjuvant ABI + bicalutamide + ADT, its level of expression was not correlated with pathologic response [23]. These contradicting findings suggest that the potential role of AR-V7 as a predictive biomarker for response to neoadjuvant ARSI-based therapy remains to be studied.…”
Section: Mckay Et Al Performed Immunohistochemistry (Ihc) In 60 Speci...mentioning
confidence: 99%
See 1 more Smart Citation
“…Efstathiou et al showed that the presence of nuclear AR-V7 correlated with residual cancer burden in the resected specimen in patients treated with a 3-month neoadjuvant ADT ± ABI [16]. Conversely, another pilot study reported that while AR-V7 expression was detected in all 16 included patients with clinically localized high-risk PCa, prior to receiving neoadjuvant ABI + bicalutamide + ADT, its level of expression was not correlated with pathologic response [23]. These contradicting findings suggest that the potential role of AR-V7 as a predictive biomarker for response to neoadjuvant ARSI-based therapy remains to be studied.…”
Section: Mckay Et Al Performed Immunohistochemistry (Ihc) In 60 Speci...mentioning
confidence: 99%
“…After the screening, a full-text review of 30 articles was performed. According to our inclusion criteria, we finally identified 20 studies eligible for systematic review [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32]. Of the twenty studies, we identified eight phase II RCTs comparing the efficacy and/or safety of ARSI-based combination therapy versus other combinations or ADT/ARSI alone (Table 1) [13][14][15][16][17][18][19][20].…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%